Increasing Age, Diabetes Mellitus and Beta Blocker Influence Heart Rate Recovery Values in Patients Undergoing Exercise Treadmill Test - Adriyawan Widya Nugraha; Cholid Tri Tjahjono; Ardian Rizal (ACI (Acta Cardiologia Indonesiana), 2019)
Background: Heart disease is the number one cause of death globally. This disease is initiation affected by autonomic dysfunction which will cause disruption of the sympathetic-parasympathetic system. Heart Rate Recovery (HRR) is used to determineautonomic dysfunction.Objective: To determine the relationship of risk factors and cardiovascular treatment to HRR values of 1 minute and 2 minutes.Methods: Cross sectional study to measure HRR 1 and 2 minute undergoing exercise treadmill test for the screening of coronary heart disease in Saiful Anwar hospital in May 2016 until September 2017. Univariate analysis was performed to determine the frequency and proportion of HRR values classified into normal groups (HRR 1 minute > 12x / minute or HRR 2 minutes > 22x / minute) and abnormal groups (HRR 2 minutes ≤ 12x / minute or HRR 2 minutes ≤ 22x / minute).We also performed bivariate analysis using comparative test (Generalized Linear Model) and correlation test (Pearson, Spearman and Eta) and multivariate linear regression analysis.Results: This study found that age, hypertension and beta blocker were significantly associated with HRR abnormalities (p<0.05). HRR 1 and HRR 2 were significantly associated with diabetes mellitus (DM) (p=0.004 and p=0.039) and beta blocker (p=0.042 and p=0.039). Then looking at the relationship of multivariate correlations found a significant correlation between age (β=-0.133, p=0.000) and DM (β=-2.617, p=0.032) at 1 minute HRR and significant correlation with age (β=-0.165, p=0.004) and beta blockers (β=-2,947, p=0.017).Conclusion: increasing of age, diabetes mellitus and beta blockers correlate with decreasing of HRR. The most influential risk factors for HRR values of 1 minute were increasing age and DM, while for HRR values of 2 minutes were increasing age and beta blockers.